An integration of historical records and genetic data to the assessment of global distribution and population structure in Octopus vulgaris - De Luca, Daniele; Catanese, Gaetano; Procaccini, Gabriele; Fiorito, Graziano (Frontiers in Ecology and Evolution, 2014)
The common octopus (Octopus vulgaris Cuvier, 1797) is one of the most widely distributed species belonging to the genus Octopus as well as an important commercially harvested species and a model organism for behavioral biology of invertebrates. It has been described for the first time in the Mediterranean Sea but it is considered a cosmopolitan species inhabiting the temperate and tropical sea of the northern and southern hemispheres. In the last few years, several species previously considered as O. vulgaris have been recognized as new species, limiting the distributional range of “vulgaris” and reinforcing the thesis of a species complex. Where it is an important fishery resource, numerous studies have been conducted in order to define its genetic structure with the purpose of managing different stocks. However, many locations are still poorly investigated from this point of view and others are under taxonomic revision to exclude or confirm its occurrence. Here we provide a summary of the current status of knowledge on distribution and genetic structure in this species in the different oceanic regions.